Enhanced dispute resolution through the use of information technology - Lodder, Arno R.; Zeleznikow, J. (Cambridge [UK] : Cambridge University Press, 2010)
'Alternative Dispute Resolution has now supplanted litigation as the principal method of dispute resolution. This overview of dispute resolution addresses practical developments in areas such as family law, plea bargaining, industrial relations and torts. The authors elaborate on the necessary legal safeguards that should be taken into account when developing technology-enhanced dispute resolution and explore a wide range of potential applications for new information technologies in dispute resolution'--
Norms for the use of technology in dispute resolution -- Developing dispute resolution processes --Technologies for supporting dispute resolution -- Advanced intelligent technologies for dispute resolution -- A three step model for online dispute resolution -- Future prospects.
Includes bibliographical references (p. 186-202) and index.
Keywords: Dispute resolution (Law) -- Automation; Dispute resolution (Law)